Ultrasound-Triggerable Coatings for Foley Catheter Balloons for Local Release of Anti-Inflammatory Drugs during Bladder Neck Dilation - Olga A. Sindeeva; Arkady S. Abdurashitov; Pavel I. Proshin; Alexey V. Kadrev; Oleg A. Kulikov; Boris M. Shaparov; Nikolay I. Sorokin; Valentin P. Ageev; Nikolay A. Pyataev; Aleksandr Kritskiy; Alexander Tishin; Armais A. Kamalov; et al. (MDPI AG, 2022)
Bladder neck contracture (BNC) is a complication of the surgical treatment of benign and malignant prostate conditions and is associated with the partial or complete blockage of urination. Correction of this condition usually requires repeated surgical intervention, which does not guarantee recovery. Balloon dilation is a minimally invasive alternative to the surgical dissection of tissues; however, it significantly reduces the patient's quality of life. Additional local anti-inflammatory treatment may reduce the number of procedures requested and increase the attractiveness of this therapeutic strategy. Here, we report about an ultrathin biocompatible coating based on polylactic acid for Foley catheter balloons that can provide localized release of Prednol-L in the range of 56-99 µg in the BNC zone under conventional diagnostic ultrasound exposure. Note that the exposure of a transrectal probe with a conventional gray-scale ultrasound regimen with and without shear wave elastography (SWE) was comparably effective for Prednol-L release from the coating surface of a Foley catheter balloon. This strategy does not require additional manipulations by clinicians. The trigger for the drug release is the ultrasound exposure, which is applied for visualization of the balloon's location during the dilation process. In vivo experiments demonstrated the absence of negative effects of the usage of a coated Foley catheter for balloon dilation of the bladder neck and urethra.